Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations and the glossy beauty of it. You must therefore keep your head scrupulously clean, and your hair well brushed and polished and healthy. [illustration] A good final rinse Every night the hair should be brushed thoroughly to remove dust and to stimulate the scalp, so encouraging the growth of hair. Then comb the hair away from the head to let the air reach the scalp. This encourages the hair to wave, specially if the comb is slightly damp. Frequent washing is most important; greasy hair should be washed as often as once a week, while dry hair can be left a fortnight or even three weeks if need be. No harm results if a good shampoo is used, however often the hair is washed, and allowing the sun and wind to get at it can do worlds of good. It is preferable to use one of the well-known proprietary shampoos, and the solution made up as directed should be poured over the wetted hair and rubbed through it and well over the scalp. If a soapless type is chosen there is no need for vinegar or lemon rinses, but if the hair is to be left really clean after the shampoo every scrap of lather must be rinsed away with warm clear water. Dry with warm towels or in the open air, never before a hot fire. Simple electric hair driers for use by hand can now be obtained at most reasonable prices. Hair-brushes and combs should be cleansed frequently. It is foolish to wash the hair and then make use of a dirty brush or comb. Hairbrushes can be washed by moving the bristles briskly in suds, beating the water, rinsing in warm and water — to harden and whiten — shaking and drying in a breeze. An old nail brush is useful for cleaning in between the teeth of combs. [illustration] Rub a little castor oil on the scalp with the tips of the fingers 9 177/5/8/4